Relay cropping of cucurbits in furrows under bed planted wheat for higher profitability - Tripathi, Subhash Chandra; Meena, Raj Pal; Chander, Subhash (Journal of Cereal Research, 2021)
A field experiment was condcuted for four consecutive seasons from 2016-17 to 2019-20 at ICAR- Indian Institute of Wheat and Barley Research, Karnal, Haryana with an objective to increase the profitability through relay crops of cucurbits under bed planted wheat crop. Eight relay crops namely musk melon, water melon, bottle guard, ridge guard, bitter guard, cucumber (kheera), cucumber (tarkakari) were planted under bed planting system with wheat. All the cucurbits were relayed in furrows at milk stage of wheat. Combined over four years analysis revealed that wheat + bottle guard produced maximum and signifiantly higher wheat equivalent yield (WEY), gross return, net return and B: C ratio, which was 80.5%, 80.5%, 227.1% and 80.0% higher than sole wheat crop, respectively. Next best profitable treatment was wheat + cucumber (tarkakari), which also produced 39.8%, 112.3% and 40.0% higher WEY, net return and B: C ratio as compared to sole wheat crop, respectively. All the relayed cucurbits were profitable than sole wheat crop and there was no adverse effect on yield attributes and wheat yield . Thus, small and marginal farmers can adopt this relayed cropping sytem to maximise their profit per unit time and space.